2022
DOI: 10.1186/s10194-022-01468-y
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 neuropsychiatric manifestations among COVID-19 survivors suffering from migraine: a case–control study

Abstract: Background The burden of post-coronavirus disease (COVID)-19 symptoms has been increasing and is of great concern in patients with pre-existing chronic medical conditions.This study aimed to delineate the post-COVID-19 neuropsychiatric symptoms among migraine patients compared to the non-migraine control group. Methods Two groups, each of 204 COVID-19 survivors, were enrolled in the study after 3 months of severe acute respiratory syndrome coronavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
14
0
3
Order By: Relevance
“…Although studies are limited, vaccinated people report less headache than those unvaccinated [30]. Several studies describe headache being more frequent in women [19,23,31–33], at a younger age [19,34,35] and in patients with personal history of migraine [23,36,37]. Concerning ethnicity, Hispanic people seem to report headache more frequently [38], although more data are needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies are limited, vaccinated people report less headache than those unvaccinated [30]. Several studies describe headache being more frequent in women [19,23,31–33], at a younger age [19,34,35] and in patients with personal history of migraine [23,36,37]. Concerning ethnicity, Hispanic people seem to report headache more frequently [38], although more data are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Association between headache and age is unclear, due to limited specific analysis [39]. Studies suggest that personal history of migraine [37,39] is not associated with persisting headache, but this finding is still controversial [36]. No conclusion can be obtained on headache prevalence during the phase after recovery from acute COVID-19 in relation to anxiety/depression, due to lack of data.…”
Section: Q1 Is Headache And/or Facial Pain a Common Symptom Of Covid-...mentioning
confidence: 99%
“…Meanwhile, patients with headache attributed to viral system infection reported a median of two points on the VAS, and patients with NDPH reported median VAS scores of five points Bold value indicates that these comparisons were statistically significant. (28). Although no data were found in the literature regarding the correlation between pain intensity and disability in long COVID, it is possible that patients with severe pain have a high degree of disability.…”
Section: Discussionmentioning
confidence: 99%
“…A case-controlled study developed in the Egypt on long COVID headache reported that patients with a previous diagnosis of migraine evaluated their actual pain with a median of 5.5 points on the VAS. Meanwhile, patients with headache attributed to viral system infection reported a median of two points on the VAS, and patients with NDPH reported median VAS scores of five points ( 28 ). Although no data were found in the literature regarding the correlation between pain intensity and disability in long COVID, it is possible that patients with severe pain have a high degree of disability.…”
Section: Discussionmentioning
confidence: 99%
“…2 Neuropsychiatric symptoms are common comorbidities of migraine and, in our study, we found that people with a worsening migraine pattern post-COVID-19 were the most susceptible to depressive symptoms, both before and after the acute phase of COVID-19, and also demonstrated a higher frequency of mood swings during the acute phase of the infection. Magdy et al 17 observed that people with migraine, compared to the controls without migraine, had…”
Section: Discussionmentioning
confidence: 99%